How Can Adolescents Get Mental Health Services Without the Availability of Professionals? A Lesson Learned from Rural Primary Health Care - Isni, Khoiriyah; Lugiana, Namira Aisyah; Trisnowati, Heni; Santri, Ichtiarini Nurullita; Qomariyah, Nurul (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The existence of a 'treatment gap' is indicated by the high frequency of individuals with mental health disorders and the low number of individuals obtaining formal treatment. It refers to the prevalence of mental problems and the proportion of people who are treated or the percentage of people who need but do not receive treatment. Aims: The study is aimed to determine the utilisation of mental health services (MHS). Methods: This study is qualitative, using a case study approach. The primary informants were six mental health workers and youth health program holders from three Primary Health Care (PHC) with the most significant number of mental health cases. Meanwhile, five youths receiving or actively undergoing treatment at the PHC served as supporting or triangulation informants. An in-depth interview guide is used in the instrument. Results: Health insurance, waiting time and duration of services, and accessibility to services play a supportive role in MHS utilization, while family and health worker support, facilities, and infrastructure do not. Adolescent and family ignorance, the presence of community stigma, the availability of human and financial resources, and health promotion media are all barriers to the utilization of MHS. Conclusion: The PHC in the Kulon Progo area is responsible for acquiring human resources, fostering collaboration across sectors, and creating health promotion media to fulfil its obligations.